Nutrients exportation by Tifdwarf bermudagrass from golf course greens - Mateus, Caroline de Moura D’Andréa; de Castilho, Regina Maria Monteiro; dos Santos, Patrick Luan Ferreira; Mota, Flávia Diniz; de Godoy, Leandro José Grava; Villas Bôas, Roberto Lyra (Ornamental Horticulture, 2020)
One of the management techniques used in greens (final areas of the holes) of golf course is the fertilizer. To correct fertilization program of these areas should know the consumption of nutrients throughout the plant cycle. The objective was to determine the export of nutrients by clipping of Tifdwarf bermudagrass (Cynodon dactylon (L.) Pers. x Cynodon transvaalensis Burtt-Davey) used in golf courses greens in the four weather seasons, as information to improve nutritional management. The research project was conducted in two golf courses in Sao Paulo State. Four greens were studied in each field, for a period of one year, using a 4x2 factorial (weather seasons x golf courses) in a completely randomized design. The production of dry matter and nutrient concentration were evaluated, and the absorption and exportation of nutrients by leaf clippings was subsequently calculated. The amount of nutrients exported by turfgrass clippings was different between the two golf courses. The summer was the season of greatest accumulation and export of nutrients in FG, except for Fe. Autumn was the season of greatest accumulation and export of nutrients in FCA, except for Mn and Zn. Considering the amount of nutrients exported by the greens clippings of the Tifdwarf bermudagrass from the two golf courses studied, the macronutrients were exported in the following order: N>K>Ca>P>S>Mg (21.8, 4.3, 2.0, 1.9, 1.8, 0.7 g m-2) and the micronutrients were exported in the following order: Fe>Zn>Mn>Cu>B (257.8, 27.4, 23.6, 7.8, 6.0 mg m-2).